THE INFLUENCE OF STRATEGIC PLANNING AND PERSONNEL COMPETENCE ON ORGANIZATIONAL PERFORMANCE OF THE TNI MATERIAL FEASIBILITY SERVICE MEDIATED BY COMPLIANCE MANAGEMENT - Sumaryadi Sumaryadi; Kusnadi Kusnadi (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
The main objective of this study is to analyze the effect of strategic planning and personnel competence on organizational performance mediated by compliance management at the material feasibility service within the Ministry of Defense and the TNI. The method used in this research is hypothesis testing using Structural Equation Modeling (SEM) based on Partial Least Square 3.0. The respondent population of this research is material feasibility inspectors who have competence and work in the Ministry of Defense and TNI. Sampling with non-probability sampling method and is a saturated sampling with a total of 50 respondents. The results showed that strategic planning had a significant but insignificant effect on organizational performance, while personnel competence had a significant effect on organizational performance. The mediating role of compliance management has a positive and significant impact on the strategic planning relationship on organizational performance. The results also show that compliance management has a positive and significant influence on the relationship between personnel competence and organizational performance. The variable that has the greatest influence on organizational performance after being mediated by Compliance management is personnel competence. The results of this study provide insight for the organization's material feasibility, in order to improve compliance management so as to improve organizational performance. The novelty in this study is to add to the role of compliance management as a mediating variable in the relationship between strategic planning and organizational performance, and in the relationship between personnel competence and organizational performance. The implication of this research is aimed at helping improve the performance of government organizations in this case the feasibility organization within the Ministry of Defense and the TNI which is tasked with ensuring the safety of personnel and material when defense materials are operated, then compliance management must be fully complied with by personnel at all levels within the organization. The limitation of the research is that it only involves two elements of strategic management, namely strategic planning and personnel competence that affect organizational performance, this becomes an opportunity for further research.